Studi Unjuk Kerja Pahat Karbida Berlapis Titanium Aluminium Nitrida (Tialn) Pada Pembubutan Kering Aluminium 6061 - S, Nopri Aji; -, Sunarto (Fakultas Teknik UMSU, 2020)
Fertilizing is one of the machining processes that uses a chisel with one eye cut to remove material from the surface of a rotating workpiece.The chisel moves in a linear direction parallel to the rotating axis of the workpiece.Some of the cutting variables will determine the quality of products such as cutting speed (Vc) The use of cut speed Variasa produces different thermal load value, and has a big effect on the cutting temperature.The purpose of the test aims to determine the impact of cut speed (Vc), motion feeding (f), and depth of cut (a) against the wear and tear of the chisel.The method used in this research is to use carbide chisels (Wc + Co) coated with Titanium aluminium Nitrida (TiAIN) coating material with DCGX 11T3 02-AI type which is used to cut the 6061 aluminum.Results obtained with cut rate (Vc) 200,270,340 m/min, motion meal (F) 0.1 mm/round, and feeding depth (a) 1.0 mm is the average side wear of the chisel is 0.08, 0.09, 0, 1 mm. The cutting speed is impacting the temperature rise.Side wear value is getting bigger ondry cuttingof 6061 aluminium material along with raising cutting speed Parameters (Vc).